2007
DOI: 10.1097/nen.0b013e3180517454
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Adrenal Gland Is Useful for Evaluating Pathology of the Peripheral Autonomic Nervous System in Lewy Body Disease

Abstract: Lewy body disease is defined as Lewy body-related neuronal degeneration involving the nigrostriatal system, limbic-neocortical system, and peripheral autonomic nervous system (PANS). We investigated whether the adrenal gland, which is evolutionarily related to sympathetic ganglia and is routinely examined in general autopsy, could be used to assess pathology of the PANS in Lewy body disease. Brains, spinal cords, and adrenal glands from 783 consecutive autopsy cases from a general geriatric hospital were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 36 publications
3
98
1
1
Order By: Relevance
“…Neuropathological studies have confirmed cardiac nerve loss showing reduced tyrosine hydroxylase (TH) and neurofilament immunostaining in epicardial nerve bundles [14], [15], [16]. In addition, Lewy bodies (intracytoplasmic inclusions composed mainly of aggregated α-synuclein), which are a classical pathological feature of PD, have been described in cardiac nerve structures including cardiac plexus [17], cardiac ganglia within the interatrial groove, epicardial bundles and nerves that innervate the myocardium, as well as in the adrenal medulla [18], [19].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Neuropathological studies have confirmed cardiac nerve loss showing reduced tyrosine hydroxylase (TH) and neurofilament immunostaining in epicardial nerve bundles [14], [15], [16]. In addition, Lewy bodies (intracytoplasmic inclusions composed mainly of aggregated α-synuclein), which are a classical pathological feature of PD, have been described in cardiac nerve structures including cardiac plexus [17], cardiac ganglia within the interatrial groove, epicardial bundles and nerves that innervate the myocardium, as well as in the adrenal medulla [18], [19].…”
Section: Introductionmentioning
confidence: 76%
“…In PD, Lewy bodies have been observed in ganglia within the adrenal medulla and periadrenal fatty tissue [18], [19], [82]. Phosphorylated α-synuclein-ir fibers have been observed as punctate or diffuse staining in the adrenal medulla of PD patients [68].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one prospective longitudinal study has examined surgically resected tissue samples and then followed the patients for PD symptom development [19]. It remains to be seen whether the sympathetic or parasympathetic branch becomes involved first or whether the pathological process commences in both branches simultaneously [23,[34][35][36]. The ultimate goal of such autopsy-based Fig.…”
Section: Discussionmentioning
confidence: 98%
“…However, findings in the adrenal bodies, the classic inclusion site of the adrenal gland, were negative. 93 Of the 18 patients in this sample with PD, all had Lewy bodies in the adrenal gland. The adrenal pathology did not correspond to any symptomatology of adrenal insufficiency, except orthostatic hypotension, which may also be due to sympathetic lesions elsewhere.…”
Section: Adrenal Glandmentioning
confidence: 98%